Experience with the modified Blalock-Taussig operation using polytetrafluoroethylene (Impra) grafts. Issue 4 (April 1983) - Kay, P H; Capuani, A; Franks, R; Lincoln, C
Abstract : Between June 1978 and January 1982, 115 patients underwent 122 subclavian artery-pulmonary artery shunts using polytetrafluoroethylene (PTFE Impra) grafts. Forty-six of the patients had a ductus dependent pulmonary circulation, the patency of which was maintained by an infusion of prostaglandin E2 in 29 cases. There were nine hospital deaths, four of which were related to shunt failure. Five patients underwent a second shunt procedure within one week of the first. There were two cases of late graft occlusion. Twelve shunts were considered to have failed. The actuarial estimate of shunt patency was 90% (+/- 3%) at two years for all patients and 74% (+/- 10%) for neonates. There was no statistically significant difference in two year shunt patency between 4 mm grafts (88 +/- 5%) and 6 mm grafts (96 +/- 3%). The modified Blalock shunt using a PTFE graft is an effective pulmonary-systemic shunt with a good short term patency.